Structural behaviour of fully coupled spar-mooring system under extreme wave loading - Saiful Islam, A.B.M. (2013)
Floating spar platform has been proven to be an economical and efficient type of offshore oil and gas exploration structure in deep and ultra-deep seas. Associated nonlinearities, coupled action, damping effect and extreme sea environments may modify its structural responses. In this study, fully coupled spar-mooring system is modelled integrating mooring lines with the cylindrical spar hull. Rigid beam element simulates large cylindrical spar hull and catenary mooring lines are configured by hybrid beam elements. Nonlinear finite element analysis is performed under extreme wave loading at severe deep sea. Morison's equation has been used to calculate the wave forces. Spar responses and mooring line tensions have been evaluated. Though the maximum mooring line tensions are larger at severe sea-state, it becomes regular after one hour of wave loading. The response time histories in surge, heave, pitch and the maximum mooring tension gradually decreases even after attaining steady state. It is because of damping due to heavier and longer mooring lines in coupled spar-mooring system under deep water conditions. The relatively lesser values of response time histories in surge, heave, pitch and the maximum mooring tension under extreme wave loading shows the suitability of a spar platform for deep water harsh and uncertain environmental conditions. Â© 2013 Copyright Â© 2013 Vilnius Gediminas Technical University (VGTU) Press.